Research on the Impact of Home Nursing Based on Intelligent Medical Internet of Things on the Quality of Life of Patients with Hemophilia. (4th May 2022) - Liu, Mengyan; Zhao, Sufang; Zhu, Xiaming; Chen, Ying
Abstract : The purpose of this paper is to study the feasibility and economic benefits of intelligent medical Internet of Things (IOT) systems for improving the quality of life of hemophilia patients, thereby reducing the risk of teratogenicity and disability for patients. This article selects 60 severe hemophilia patients who were followed up in our hospital from 2018 to 2019 as the research object. In the intelligent medical system, the Gaussian mixture model discretization algorithm is used to preprocess patient data collection. The observation group uses the intelligent medical system to implement home nursing for the patients, and the control group uses ordinary home nursing. This paper evaluates the quality of life of the two groups of patients 6 months after the intervention, including self-care ability, transfer function, and home nursing cognitive ability. The research results show that the home nursing based on smart medical IOT proposed in this paper is feasible and effective for improving the quality of life of patients. It can effectively improve the patient's self-care ability and joint functions and has important reference value for the development of intelligent medical IOT equipment.